Taxonomic and ecological aspects of Myrceugenia mesomischa (Myrtaceae), an endemic tree from southern Brazil - Setubal,Robberson Bernal (2011)
Abstract Myrceugenia mesomischa (Burret) D. Legrand & Kausel (Myrtaceae), a tree species poorly cited in floristic and phytosociological surveys in its area of known occurrence, was recorded as one of the species with the highest importance value in a fragment of Araucaria forest in São Francisco de Paula municipality, Rio Grande do Sul state, Brazil. The species was abundant in the understory strata of the forest, showing the highest frequency and density of the survey. Considering the paucity of data on the species, its degree of rarity and endemism (occurring only in the states of Rio Grande do Sul and Santa Catarina, Brazil), more studies are needed to evaluate the true current state of conservation of populations of this species.